Agricultural cooperatives and the failure to achieve commercialization of agriculture in Nepal: A case study of the Chitwan district - Dinesh Dhakal; Peter R. Mueser (Research in Globalization, 2023)
For more than two decades, the government of Nepal has invested resources in agricultural cooperatives, prioritizing cooperatives as part of a strategy for poverty reduction. Agricultural cooperatives have a stated goal of improving family incomes through the commercialization of agriculture by increasing agricultural production and supporting the marketing of produce. However, there is mounting evidence that these goals have not been met and that farming households remain largely disconnected from agricultural markets. The analysis here addresses the question: Why have agricultural cooperatives in Nepal failed in facilitating the commercialization of agriculture? Based on a household survey of a stratified sample of 200 cooperative member households in the Chitwan district, the current research investigates the role of agricultural production in household finances, considers services provided by cooperatives and the reasons households join cooperatives, household relations with cooperatives, along with information about the residential circumstances of households. The survey includes both open-ended and close-ended questions, which are coded into categories. These are supplemented by key informant interviews (KII) using a purposive sample of 37 agricultural managers in cooperatives whose members were part of the household survey. Based on interviews using open-ended questions, these surveys identified the role managers see agricultural cooperatives filling, the obstacles they face, and their view of the political and economic environment. We present a set of hypotheses, which we test using one-sample t-tests, two-sample paired t-tests, and two-sample (unpaired) t-tests based on household responses. We confirm that agricultural commercialization is limited by the small scale of agricultural production at the household level, that services provided by cooperatives provide little support for marketing member produce, and that households have multiple ties to cooperatives and other mutual assistance organizations, which dilutes their commitment in agricultural cooperatives. We do not confirm the hypothesis that households that rely more heavily on agriculture differ substantially in these respects. Based on responses to our open-ended questions, we find that families consider financial services the most valuable services provided by cooperatives. In the key informant interviews, managers observe that cooperatives depend on revenue from financial services to cover operating costs. They recognize that cooperatives have made little progress in their goal of commercializing agriculture, and they believe that additional government support will be necessary for market-based agriculture to contribute substantially to household income. We believe our results imply that in order for agricultural cooperatives to succeed in their goals of increasing the commercialization of agricultural production and increasing farm family incomes, there will need to be concerted efforts by government, and a reorientation of the attitudes of households and cooperatives.
Keywords: 330; Cooperatives; Financial services; Marketing; Poverty reduction